Synthesis and characterization of nickel boride nanoparticles for energy conversion catalyst materials – the effect of annealing temperature - Kharboot, Layla Haythoor; Hui, Xin Lim; Abu Bakar, Tuty Asma; Mohd Najib, Abdillah Sani; Mohd Nor, Nur Safwati; Nordin, Norhuda Hidayah; Fadil, Nor Akmal (Elsevier, 2024)
In the recent technology development, fuel cell has been widely used in many applications, including transportation and industry. Platinum catalysts are used to catalyst the reaction at the oxygen electrode, but they are expensive and has limited supply. A nickel-boron nanoparticle catalyst is proposed as a substitute for fuel cell catalyst material. The objectives are to evaluate the effect of the annealing process and to determine the characteristics of the annealed nanoparticles using scanning electron microscopy - energy dispersive X-ray (SEM-EDS), inductively coupled plasma optical emission spectroscopy (ICP-OES) analysis, total organic carbon (TOC) analysis and X-ray diffraction (XRD). A wet chemical method was used to synthesize nickel-boron nanoparticles by chemical reduction (co-reduction) of nickel chloride and sodium borohydride. As-synthesized nickel-boron nanoparticles were annealed at temperatures of 200, 300, 400, 500, and 700 °C in an argon atmosphere for 2 h. From the experimental results, nickel-boron nanoparticles annealed at 300 °C with equal dispersion of crystalline Ni and crystalline Ni3B showed the highest catalyst performance. The yield of nickel-boron nanoparticles sized 1.1364 nm was smaller than in the literature (37 nm). The size of Ni-B nanoparticles was calculated by using the Scherrer equation with the values of full width half maximum (FWHM) obtained by peak fitting following the Gaussian model. Smaller Ni-B nanoparticles have a higher surface-area-to-volume ratio, which increases the exposure of the active sites (crystalline Ni and crystalline Ni3B phase) to the reactants (methanol) and improves catalytic activity.